The Relationship of Business Management Practices on Financial Performance: Evidence from Quick-Service Restaurants in Mandaluyong, Philippines - Eupeña, John Arthur; Neiz, Sophia Angela A.; Ocampo, Alyssa G.; Guballo, Jayvie O. (The Indonesian Institute of Science and Technology Research, 2025)
The Philippines is home to a thriving food service business encompassing a wide range of facilities, including restaurants, fast-food chains, cafes, and tiny booths and kiosks. Economic growth and employment are of profound importance in the fast-food industry. The study aims to investigate the significant and positive relationship between business management practices and financial performance. To examine the relationship between business management practices and financial performance as factors, a correlational research design and Pearson's r were utilized in the research process. Due to the study's limitations, other researchers might also consider examining other variables through causal-comparative research. The study's outcomes indicate that methods about finance, human resources, marketing, and operations have a statistically positive and significant relationship with financial performance. These restaurants are considering addressing more difficulties or utilizing a paper to further develop their strategies and practices to improve their economic performance.